(untitled) (Journal of the College of Basic Education, 2025)
Dialysis patients are at risk on imbalance (deficiency and a accumulation) of essential trace elements based on diet, decreased kidney function and removal by dialysis. The aim of this study was to estimate the Cu, Zn and lead levels in patients with renal failure before and after their dialysis and healthy group. Method: this study included fifty chronic renal failure patients (CRF) collected from Al-kindy teaching hospital, Baghdad compared with fifty healthy as a control group. Cu, Zn, Pb concentration were measured by atomic absorption spectrophotometer in serum of CRF patients per and post dialysis and control group. Result:The results showed a significant increase at p ≤0.05 in Zn and Pb concentration in serum of pre and post CRF patients compared with control group. While a significant decrease in Cu concentration in serum of CRF patients before and after dialysis compared with control group. Conclusion: there was a significant decrease of Cu level in patients (before and after dialysis) compared with healthy group. While the concentration of Zn and Pb were significant increase in patients (before and after dialysis).